THE GLORY OF THE SCHOLAR: THE NEXUS OF BEAUTY AND INTELLECT IN CHINESE AND RABBINIC LITERATURE. - Amihay, Aryeh; Lupeng Li (Philosophy East & West: A Quarterly of Comparative Philosophy, 2023)
The article focuses on the relationship between beauty and intellect in ancient Chinese and Jewish texts, particularly in Confucian and rabbinic traditions. The article seeks to compare and explore shared themes in these civilizations and highlight their resistance to singular interpretations or consistent outlooks on beauty and intellect.